2006
DOI: 10.1103/physrevlett.96.105702
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Induced Phase Transitions in the Cd-Yb Periodic Approximant to a Quasicrystal

Abstract: The phase study of a Cd-Yb 1/1 approximant crystal over a wide pressure and temperature range is crucial for the comparison study between periodic and quasiperiodic crystals. The Cd(4) tetrahedra, the most inner part of the atomic clusters, exhibited various structural ordering in the orientation sensitive to pressure and temperature. Five ordered phases appeared in a P-T span up to 5.2 GPa and down to 10 K. The propagation direction of ordering alternated from [110] to <111> to at about 1.0 GPa and again to [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 14 publications
3
35
0
Order By: Relevance
“…a very large unit cell with a lattice parameter of about 5.5 nm. The resulting pressure-temperature phase diagram is different from that of Cd 6 Yb, which was reported by Watanuki et al (2006). …”
mentioning
confidence: 66%
See 1 more Smart Citation
“…a very large unit cell with a lattice parameter of about 5.5 nm. The resulting pressure-temperature phase diagram is different from that of Cd 6 Yb, which was reported by Watanuki et al (2006). …”
mentioning
confidence: 66%
“…A similar dynamical flexibility was observed in the quasicrystal [17] , although in that case the freezing of the tetrahedra occurs progressively, as in a glassy system. Watanuki et al (2006) have investigated the phase diagram of Cd 6 Yb at simultaneous LT and high-pressures and observed five new superstructure schemes, labeled from I to V, as a function of the applied pressure up to 5.2 GPa [18]. They found that the ordering scheme is sensitive to the temperature and pressure: at ambient pressure the LT superstructure (phase I) has a propagation vector along [110] direction of the HT phase, breaking the cubic symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…Watanuki et al have reported that T c increases under high pressure for Cd 6 Yb, indicating that the reduction of the space inside the 2nd dodecahedron shell promotes ordering of the tetrahedra [17]. One interesting fact concerning this point is that T c does not increase with the reduction of the lattice constant, i.e., the reduction of the space inside the 2nd dodecahedron shell, as seen in Figs.…”
Section: Complex Metallicmentioning
confidence: 52%
“…A comparable phase transition is that in the decagonal quasicrystal, AlCoNi [37]. Another example of a phase transition related to quasicrystals is one in an approximant of the quasicrystal, CdYb [38]. For phase transitions from a quasicrystal to a modulated quasicrystal, one may use the same technique as for the transition from a lattice periodic structure to an incommensurate modulated phase [39,40].…”
Section: Phase Transitionsmentioning
confidence: 99%